Atividade antiinflamátoria, antiagregante plaquetária e efeitos centrais de alfa e beta amirina isolada de protium heptaphyllum aubl march - Aragão, Gislei Frota (2004)
The species Protium heptaphyllum Aubl. March. belonging to the family Burseraceae is common in several areas of Brazil, where is known as almecega or white pitch. The plant is used popularly an anti-inflammatory and antiulcer. The objective of the present work was to study the pharmacological effects of a isomeric mixture of two triterpenes: alpha and beta amyrin (AMI) isolated from Protium heptaphyllum. The pharmacological activities (antinociceptive, antiedematogenic, central and antiaggregant), of AMI were studied in mice, using several experimental models. AMI inhibited the abdominal contractions induced by acetic acid in 73 and 94% in the doses of 10 and 50 mg/Kg, i.p., respectively, when compared to control. In the formalin test, the effect was observed in the two phases, with inhibitions of 37 and 51 % (1st phase) and 60 and 73% (2nd phase) after the administration of 10 and 50 mg/Kg,i.p., respectively. In the hot plate test, AMI increased the latency to the thermal stimulus in the dose of 50 mg/Kg, i.p., with 62, 71 and 25% inhibitions after 30, 60 and 90 min, respectively). The antinociceptive effect is mainly peripheral and independent of the opioid system. In the models of paw edema induced by carrageenan and dextran in mice, AMI demonstrated a antiedematogenic dose-dependent effect, in the two models. The healing effect of AMI, when administered after the formation of the edema was also evaluated with the two edematogenic agents (carrageenan and dextran), AMI was more effective to treat the edema provoked by the carrageenan. The antiedematogenic effect of AMI was not potentiated in the presence of indometacin (cyclooxigenase inibitor), however the association with thalidomide, a strong inhibitor of the liberation of TNF-alfa, resulted in a synergistic effect and therefore larger than the effect of each one of the drugs separately, indicating that the mechanism of action involves inhibition of levels of TNF-alfa. The central effect of AMI (the decrease of the exploratory activity and the rearing frequency in the Open Field test) were also dose-dependently. In the elevated plus maze test it was observed an anxiolytic effect with AMI in the dose of 50 mg/Kg, i.p. The inhibition of platelet was observed in human platelets, where AMI inhibited the aggregation induced by following agonists: ADP (3mcM), collagen (10mcM) and arachidonic acid (150mcg/mL). This effect was potentiated by acetylsalicylic acid (a ciclooxigenase inhibitor), mainly by the ADP agonist. The results of the work allowed to conclude us that AMI have analgesic, anti-inflammatory (profilatic and terapeutic effects), sedative, anxiolytic activities as well as also an antiaggregation affect of human platelets.